The Rice Actin-Binding Protein RMD Regulates Light-Dependent Shoot Gravitropism . Issue 2 (15th August 2019) - Song, Yu; Li, Gang; Nowak, Jacqueline; Zhang, Xiaoqing; Xu, Dongbei; Yang, Xiujuan; Huang, Guoqiang; Liang, Wanqi; Yang, Litao; Wang, Canhua; Bulone, Vincent; Nikoloski, Zoran; et al.
Abstract : Actin binding protein RMD is involved in controlling shoot negative gravitropism in a light-dependent manner. Abstract: Light and gravity are two key determinants in orientating plant stems for proper growth and development. The organization and dynamics of the actin cytoskeleton are essential for cell biology and critically regulated by actin-binding proteins. However, the role of actin cytoskeleton in shoot negative gravitropism remains controversial. In this work, we report that the actin-binding protein Rice Morphology Determinant (RMD) promotes reorganization of the actin cytoskeleton in rice ( Oryza sativa ) shoots. The changes in actin organization are associated with the ability of the rice shoots to respond to negative gravitropism. Here, light-grown rmd mutant shoots exhibited agravitropic phenotypes. By contrast, etiolated rmd shoots displayed normal negative shoot gravitropism. Furthermore, we show that RMD maintains an actin configuration that promotes statolith mobility in gravisensing endodermal cells, and for proper auxin distribution in light-grown, but not dark-grown, shoots. RMD gene expression is diurnally controlled and directly repressed by the phytochrome-interacting factor-like protein OsPIL16. Consequently, overexpression of OsPIL16 led to gravisensing and actin patterning defects that phenocopied the rmd mutant. Our findings outline a mechanism that links light signaling and gravity perception for straight shoot growth in rice.